Escrita, comunicação e saber emancipatório na obra de intelectuais negras : enfrentamento ao racismo epistêmico - Adriana de Oliveira Costa (2025)
This dissertation analyzed the written communication black women intellectuals, focusing on Sueli Carneiro, female author of “Device of raciality: the construction of the other non-being as the foundation of being” (2023) and Grada Kilomba, who wrote “Memórias da Plantação” (2019), the two female authors discuss the fight against epistemic racism and intersectional prejudices in their research. The literary writing of these women relates to the idea of ​​Michel Foucault's Writing of the Self (2004), which connects writing, knowledge and emancipation, as a form of writing that black women intellectuals employ to connect the experiences of the fight against racism. and question racial and social contexts. Studies carried out by black thinkers contest negative ideas that exclude and oppress their knowledge. These female authors present communication strategies that promote the coexistence of various types of knowledge, establishing an environment of confluence based on criticism of the universal power of academia in relation to its academic voices. These female authors encourage the examination of various situations, allowing their research to show the characteristics of communities fighting against racism, which marks the need to understand, analyze and interpret their literary works from different angles, challenging established universal academic power.